A water-based adhesive for laminating medical surgical gowns and a preparation method thereof

By combining VAE emulsion and other additives, a water-based glue suitable for medical surgical gown fit was prepared, which solved the stability and biocompatibility problems of existing water-based glue in medical surgical gown applications, and achieved high viscosity, stability and flexibility.

CN115895517BActive Publication Date: 2025-04-11SHANGHAI ROCKY ADHESIVES CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211406186.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-10
Publication Date
2025-04-11
Estimated Expiration
2042-11-10

AI Technical Summary

Technical Problem

In the application of medical surgical gowns, existing water-based glues are difficult to meet the requirements of high strength, good weather resistance, no skin allergy and good initial viscosity, and there are problems of poor stability and low biocompatibility.

Method used

By combining the first VAE emulsion with a solid content of 55-65%, a particle size of 0.5-1.0 μm and a second VAE emulsion with a viscosity of 1000-4000 mPa·s and a glass transition temperature of -20-0°C, a water-based glue suitable for medical surgical gown fitting was prepared.

Benefits of technology

It improves the viscosity and stability of water-based glue, enhances its flexibility and high and low temperature stability, is suitable for the fit of medical surgical gowns, and is friendly to the human body and the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003936709950000091
    Figure BDA0003936709950000091
Patent Text Reader

Abstract

The present invention relates to the technical field of water-based adhesives, in particular to the field of IPC C09J4, and more specifically to a water-based adhesive for medical surgical gowns and a preparation method thereof. The water-based adhesive for medical surgical gowns includes, by weight, 20-75 parts of VAE emulsion, 2-10 parts of plasticizer, 0.02-0.10 parts of emulsifier, 0.05-0.15 parts of defoamer, and 0.05-0.15 parts of preservative. The water-based adhesive for medical surgical gowns has high shear strength and good stability, and has a fast curing rate, and is harmless to the human body and the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water-based adhesives, in particular to the field of IPC C09J4, and more specifically to a water-based adhesive for laminating medical surgical gowns and a preparation method thereof. Background Art

[0002] Water-based adhesives are low-cost, environmentally friendly and easy to process, making them widely used. Medical surgical gowns have cuff buckles and pockets, which need to be attached to the gowns using water-based adhesives. The water-based adhesives need to have high strength, good weather resistance, no skin allergies, good initial adhesion, etc. However, it is difficult for the water-based adhesives currently on the market to fully meet this requirement.

[0003] In the prior art, a patent application document with application publication number CN108546529A discloses a method for preparing an adhesive by cross-linking modified VAE emulsion, which improves the water resistance, flexibility and viscosity of the VAE emulsion. However, toluene is used in its raw materials, and toluene is a harmful substance that can cause harm to the human body.

[0004] The patent application document with application publication number CN112011229A discloses a water-based widely applicable packaging adhesive and a preparation method thereof, which is prepared by mixing two VAE emulsions with different viscosities, and can improve the bonding performance of the water-based adhesive, which is conducive to its application in packaging adhesive, but its biocompatibility is low.

[0005] VAE emulsion has good bonding strength and flexibility, is environmentally friendly and easy to process, but its poor stability and low viscosity limit its application. Therefore, it is necessary to develop a water-based adhesive with high shear strength, good stability, fast curing rate, and no harm to the human body or the environment. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present invention provides a water-based adhesive for bonding medical surgical gowns. The raw materials for preparation include, by weight: 20-75 parts of VAE emulsion, 2-10 parts of plasticizer, 0.02-0.10 parts of emulsifier, 0.05-0.15 parts of defoaming agent, and 0.05-0.15 parts of preservative.

[0007] Preferably, the VAE emulsion includes a first VAE emulsion and a second VAE emulsion.

[0008] The solid content of the first VAE emulsion is 55-65%, and the particle size is 0.5-1.0 μm; more preferably, the solid content of the first VAE emulsion is 59-61%, and the particle size is 0.9 μm.

[0009] In some preferred embodiments, the first VAE emulsion may be commercially available, such as Celvolit 1405 produced by Celanese (Nanjing) Chemical Co., Ltd.

[0010] The applicant unexpectedly discovered that the use of a VAE emulsion with a solid content of 55-65% and a particle size of 0.5-1.0 μm as the first VAE emulsion can improve the viscosity and stability of the water-based adhesive. This may be because a high solid content will increase the content of the colloid particles in the same volume, and the small particle size of the emulsion has a large specific surface area, which will increase the total surface area in the system example, thereby increasing the movement resistance and interaction between the particles, and improving the viscosity and stability of the water-based adhesive. However, if the particle size is too small, agglomeration will occur, which will affect the stability of the water-based adhesive. Therefore, a VAE emulsion with a solid content of 55-65% and a particle size of 0.5-1.0 μm is selected as the first VAE emulsion, but its glass transition temperature is high, which will result in large rigidity of the molecular chain in the water-based adhesive, low flexibility, slow film formation speed and hard film, which is not conducive to application in medical surgical gowns.

[0011] The viscosity of the second VAE emulsion is 1000-4000 mPa·s (25°C), and the glass transition temperature is -20-0°C; more preferably, the viscosity of the second VAE emulsion is 1500-3000 mPa·s (25°C), and the glass transition temperature is -18°C.

[0012] In some preferred embodiments, the second VAE emulsion may be commercially available, such as Celvolit 1475 produced by Celanese (Nanjing) Chemical Co., Ltd.

[0013] The weight ratio of the first VAE emulsion to the second VAE emulsion is 1:(1-5); more preferably, it is 1:3.

[0014] The applicant unexpectedly discovered that the second VAE emulsion with a viscosity of 1000-4000mPa·s (25°C) and a glass transition temperature of -20-0°C can be used to compound with the first VAE emulsion, while ensuring the viscosity of the water-based adhesive, and also making it flexible, easy to process, and having good high and low temperature stability. This is because the two different VAE emulsions have different chain lengths and configurations, which can increase their degree of cross-linking, so that there is no need to add additional monomers, and it can also have good viscosity and high and low temperature stability. Moreover, when the content of the second VAE in the raw material is higher than that of the first VAE emulsion, and the weight ratio of the first VAE emulsion to the second VAE emulsion is 1: (1-5), the prepared water-based adhesive has good flexibility and low solid content, and the prepared water-based adhesive is easier to wet and spread, the molecules are in close contact, the peel strength is high, the processing performance is better, and the film-forming speed is fast, which makes it have a wider range of applications, especially suitable for medical surgical gown bonding adhesive.

[0015] The plasticizer is selected from one or more of dipropylene glycol dibenzoate, phthalates, di(2-ethylhexyl) phthalate, dibutyl phthalate, aliphatic dibasic acid esters, and diethyl phthalate; more preferably, dipropylene glycol dibenzoate.

[0016] In some preferred embodiments, the plasticizer may be commercially available, such as Benzoflex 988 produced by BASF Corporation of the United States.

[0017] The emulsifier is selected from one or more of anionic emulsifiers, cationic emulsifiers, and nonionic emulsifiers; more preferably, it is an anionic emulsifier.

[0018] The anionic emulsifier is selected from one or more of sodium laurate, sodium cyclohexane, sodium stearate, lauric acid soap, rosin oil soap, sodium alkylbenzene sulfonate, sodium didodecylphenyl ether disulfonate, dioctyl sodium sulfosuccinate, and sodium dodecyl sulfate; more preferably, dioctyl sodium sulfosuccinate.

[0019] The mass of the emulsifier is 0.01-0.1% of the mass of the VAE emulsion.

[0020] The applicant unexpectedly discovered that the use of dioctyl sodium sulfosuccinate as an emulsifier can improve the stability of water-based adhesives. This may be because as the water-based adhesive is placed for a longer time, the molecular chains in the emulsion are easily entangled into a mass, causing the emulsion to gel and affecting its stability. Adding a certain amount of dioctyl sodium sulfosuccinate not only has good compatibility with VAE emulsions, but also has little pollution to the environment and harm to people. Dioctyl sodium sulfosuccinate not only enters the surface layer for directional arrangement, reduces the intermolecular forces, and thus reduces the surface tension, but also affects the double electric layer structure of the latex particles, forms a steric hindrance, improves the dispersibility of VAE molecules in water, and thus improves the water resistance and stability of the water-based adhesive. However, adding too much emulsifier has little effect on the surface tension, and also affects the viscosity of the water-based adhesive, thereby affecting the stability of the water-based adhesive. When the mass of the emulsifier is 0.01-0.1% of the mass of the VAE emulsion, the water-based adhesive obtained has high viscosity and excellent stability.

[0021] The defoamer is selected from one or more of mineral oil defoamers, silicone defoamers, polyether defoamers, powder defoamers, fermentation defoamers, and water treatment defoamers; more preferably, it is a mineral oil defoamer.

[0022] The density of the mineral oil defoamer is 0.5-1.5 g / cm 3 , viscosity is 300-500mPa·s; further preferably, the density of the mineral oil defoamer is 0.87g / cm 3, viscosity is 450mPa·s.

[0023] In some preferred embodiments, the mineral oil defoamer can be commercially available, such as the one produced by BASF Corporation of the United States. MO NXZ AG.

[0024] The applicant found that the density was 0.5-1.5 g / cm 3 , and the mineral oil defoamer with a viscosity of 300-500mPa·s can improve the stability of the system while maintaining the viscosity of the water-based adhesive. This may be due to the synergistic effect of the defoamer and the emulsifier. The hydroxyl and ether bonds on the defoamer molecules carry positive charges with water through hydrogen bonds, and electrostatic effects occur between ions, which reduces the repulsion between hydrophilic groups and enhances the emulsification ability of the emulsifier, thereby improving the stability of the system. In addition, the mineral oil defoamer has good compatibility with VAE emulsions. When used in the water-based adhesive system, it can play a role in stabilizing and eliminating bubbles, so that the prepared water-based adhesive has good uniformity and no bubbles after curing, thereby improving the shear strength of the water-based adhesive.

[0025] Preferably, the active ingredient concentration of the preservative is 0.1-3%; more preferably, it is 1.5%.

[0026] In some preferred embodiments, the preservative may be commercially available, such as KATHONò LXE produced by Rohm and Haas Company.

[0027] The preservative with an active ingredient concentration of 0.1-3% has excellent compatibility with VAE, not only has high antiseptic performance, but also has good bactericidal effect, and does not contain harmful substances such as formaldehyde. When the weight of the preservative is 0.05-0.15% of the system weight, it not only has good bactericidal and antiseptic effects, but also is harmless, will not cause allergic reactions, and will quickly and completely decompose into harmless substances, which has certain environmental protection significance. In addition, it is low in price and has high economic benefits.

[0028] The weight of the preservative is 0.05-0.2% of the system weight.

[0029] Preferably, the raw materials for preparation further include acrylic emulsion; the weight of the acrylic emulsion is 3-5% of the total weight of the raw materials; further preferably, it is 4%.

[0030] Preferably, the solid content of the acrylic emulsion is 20-40%, and the glass transition temperature is 30-50°C; further preferably, the solid content of the acrylic emulsion is 30%, and the glass transition temperature is 43°C.

[0031] In some preferred embodiments, the acrylic emulsion may be commercially available, such as Joncryl 95 produced by BASF.

[0032] A second aspect of the present invention provides a method for preparing the pressure-sensitive hot melt adhesive as described above, comprising the following steps:

[0033] After uniformly mixing VAE emulsion, acrylic emulsion and plasticizer, add emulsifier and preservative, and after uniformly mixing, add defoamer to obtain the product.

[0034] Beneficial effects:

[0035] 1. By selecting a VAE emulsion with a solid content of 55-65% and a particle size of 0.5-1.0 μm as the first VAE emulsion, the viscosity and stability of the water-based adhesive can be improved.

[0036] 2. By selecting a second VAE emulsion with a viscosity of 1000-4000 mPa·s (25°C) and a glass transition temperature of -20-0°C to compound with the first VAE emulsion, the viscosity of the water-based adhesive can be ensured while also making it flexible, easy to process, and having good high and low temperature stability.

[0037] 3. When the weight ratio of the first VAE emulsion to the second VAE emulsion is 1:(1-5), the prepared water-based adhesive has good flexibility and low solid content, is easier to wet and spread, has close molecular contact, high peel strength and better processing performance, and fast film-forming speed, which makes it have a wider range of applications and is particularly suitable for use in medical surgical gown bonding adhesives.

[0038] 4. By selecting a density of 0.5-1.5g / cm 3 , and the mineral oil defoamer with a viscosity of 300-500mPa·s can improve the stability of the system while maintaining the viscosity of the water-based glue.

[0039] 5. The water-based adhesive for medical surgical gowns prepared by the present invention is not only suitable for medical surgical gowns, but also suitable for cigarette adhesives, box sealing, soft packaging, textiles, paper product processing, envelopes, non-woven fabrics and other fields. DETAILED DESCRIPTION

[0040] Example

[0041] Example 1

[0042] Example 1 provides a water-based adhesive for bonding medical surgical gowns. The raw materials for its preparation include, by weight: 60 parts of VAE emulsion, 5 parts of plasticizer, 0.05 parts of emulsifier, 0.1 parts of defoaming agent, and 0.1 parts of preservative.

[0043] The VAE emulsion includes a first VAE emulsion and a second VAE emulsion.

[0044] The weight ratio of the first VAE emulsion to the second VAE emulsion is 1:3.

[0045] The solid content of the first VAE emulsion is 59-61%, and the particle size is 0.9 μm.

[0046] The first VAE emulsion was purchased from Celanese (Nanjing) Chemical Co., Ltd. as Celvolit 1405.

[0047] The viscosity of the second VAE emulsion is 1500-3000 mPa·s (25° C.), and the glass transition temperature is -18° C.

[0048] The second VAE emulsion was purchased from Celanese (Nanjing) Chemical Co., Ltd. as Celvolit 1475.

[0049] The plasticizer is dipropylene glycol dibenzoate.

[0050] The plasticizer was purchased from a supplier, Benzoflex 988 produced by BASF Corporation of the United States.

[0051] The emulsifier is selected from anionic emulsifiers; the anionic emulsifier is selected from dioctyl sodium sulfosuccinate.

[0052] The emulsifier was purchased from supplier Wuhan Kanosi Technology Co., Ltd., and was produced as OT-75.

[0053] The defoamer is selected from mineral oil defoamers.

[0054] The density of the mineral oil defoamer is 0.87 g / cm 3 , viscosity is 450mPa·s.

[0055] The mineral oil defoamer was purchased from BASF Corporation in the United States. MO NXZAG.

[0056] The active ingredient concentration of the preservative is 1.5%.

[0057] The preservative was purchased from supplier Rohm and Haas Company and was produced as KATHONò LXE.

[0058] The raw materials for preparation also include acrylic emulsion; the weight of the acrylic emulsion is 4% of the total weight of the raw materials.

[0059] The acrylic emulsion has a solid content of 30% and a glass transition temperature of 43°C.

[0060] The acrylic emulsion was purchased from supplier BASF Corporation as Joncryl 95.

[0061] A method for preparing a medical surgical gown with a water-based adhesive comprises the following steps:

[0062] The first VAE emulsion, the second VAE emulsion, the acrylic emulsion and the plasticizer are mixed uniformly, an emulsifier and a preservative are added, mixed uniformly, a defoamer is added, and mixed uniformly to obtain the product.

[0063] Example 2

[0064] Example 2 provides a water-based adhesive for laminating medical surgical gowns. The specific implementation method is the same as that of Example 1, except that the VAE emulsion is the first VAE emulsion.

[0065] Example 3

[0066] Example 3 provides a water-based adhesive for bonding medical surgical gowns. The specific implementation method is the same as that of Example 1, except that the weight ratio of the first VAE emulsion to the second VAE emulsion is 2:1.

[0067] Example 4

[0068] Example 4 provides a water-based adhesive for bonding medical surgical gowns. The specific implementation method is the same as that of Example 1, except that the mass fraction of the emulsifier is 0.12 parts.

[0069] Example 5

[0070] Example 5 provides a water-based adhesive for bonding medical surgical gowns. The specific implementation method is the same as that of Example 1, except that the weight percentage of the preservative is 0.2 parts.

[0071] Performance Testing Methods

[0072] 1. Peel strength

[0073] The water-based adhesive was applied to the medical surgical gown prepared in Examples 1-5 on a layer of non-woven fabric of the medical surgical gown, and another layer of non-woven fabric was covered on top. After standing for 24 hours, the peel strength was measured using the national standard GB / T 2792-2014, and the results are recorded in Table 1.

[0074] 2. Weather resistance

[0075] Low temperature resistance:

[0076] The water-based adhesive for bonding the medical surgical gowns prepared in Examples 1-5 was applied between two pieces of non-woven fabrics and placed for 24 hours until they were completely bonded. They were then placed in an environment of -10°C for 24 hours, taken out, and the two pieces of non-woven fabrics were torn apart to see if they could be torn apart smoothly. If they could not be torn apart smoothly, the non-woven fabric was broken, which indicated that the peel strength between the two pieces of non-woven fabrics was high and the low-temperature stability was good. The results are recorded in Table 1.

[0077] High temperature resistance:

[0078] The water-based adhesive for bonding the medical surgical gowns prepared in Examples 1-5 was applied between two pieces of non-woven fabrics and placed for 24 hours until they were completely bonded. They were then placed in an environment of 70°C for 24 hours, taken out, and the two pieces of non-woven fabrics were torn apart to see if they could be torn apart smoothly. If they could not be torn apart smoothly, the non-woven fabric was broken, which indicated that the peel strength between the two pieces of non-woven fabrics was high and the high-temperature stability was good. The results are recorded in Table 1.

[0079] 3. Biocompatibility

[0080] For the medical surgical gowns prepared in Examples 1-5 and the water-based adhesive, the cytotoxicity experiment of medical tape was carried out using the ISO 10993-5:2009 method, and the 100% sample extract was compared with the blank control. The cell viability exceeded 80%, which indicated that the medical surgical gowns and the water-based adhesive had potential toxic effects and passed the biocompatibility test. The results are recorded in Table 1.

[0081] Table 1

[0082]

Claims

1. A water-based adhesive for laminating medical surgical gowns, characterized in that: The raw materials for its preparation include, by weight: 20-75 parts of VAE emulsion, 2-10 parts of plasticizer, 0.02-0.10 parts of emulsifier, 0.05-0.15 parts of defoamer, and 0.05-0.15 parts of preservative; The VAE emulsion includes a first VAE emulsion and a second VAE emulsion; The weight ratio of the first VAE emulsion to the second VAE emulsion is 1:(1-5); The solid content of the first VAE emulsion is 59-61%, and the particle size is 0.9 μm; the viscosity of the second VAE emulsion is 1000-4000 mPa·s (25° C.), and the glass transition temperature is -20-0° C.; the emulsifier is dioctyl sodium sulfosuccinate, and the mass of the emulsifier is 0.01-0.1% of the mass of the VAE emulsion.

2. The water-based adhesive for laminating medical surgical gowns according to claim 1, characterized in that: The plasticizer is selected from one or more of dipropylene glycol dibenzoate, phthalate, di(2-ethylhexyl) phthalate, dibutyl phthalate, aliphatic dibasic acid esters, and diethyl phthalate.

3. A water-based adhesive for laminating medical surgical gowns according to any one of claims 1-2, characterized in that: The defoamer is selected from one or more of a mineral oil defoamer, a silicone defoamer, a polyether defoamer, a powder defoamer, a fermentation defoamer, and a water treatment defoamer.

4. The water-based adhesive for laminating medical surgical gowns according to claim 3, characterized in that: The density of the mineral oil defoamer is 0.5-1.5 g / cm 3 , viscosity is 300-500mPa·s.

5. A method for preparing a water-based adhesive for laminating medical surgical gowns according to any one of claims 1 to 4, characterized in that: The following steps are involved: After VAE emulsion and plasticizer are evenly mixed, emulsifier and preservative are added, after evenly mixed, defoamer is added to obtain the product.

Citation Information

Patent Citations

  • Crosslinking method of modifying VAE emulsion to prepare adhesive

    CN108546529A

  • Water-based eurytopic packaging adhesive and preparation method thereof

    CN112011229A